(untitled) (Scottish Historical and Archaeological Internet Reports, 2008)
The results of the project and discussions of the findings are presented below in a synthetic narrative based on the three main evidence strands for occupation in the valley. These comprise the burnt mound deposits, wood and inundations, the moated enclosure and its environs.